Evaluation of the Factors Contributing to Fibrin–dependent Plasminogen Activation - Mosesson, Michael W.; Siebenlist, Kevin R.; Voskuilen, Marijke; Nieuwenhuizen, Willem (Thrombosis and Haemostasis, 1998)
Polymerized fibrin strongly enhances tissue plasminogen activator (tPA)-mediated plasminogen activation, concomitant with exposure of ‘fibrin-specific’ epitopes at ‘Aα148-160’ and ‘γ312-324’. To investigate which aspects of polymerization are involved in these activities, we explored the fibrin polymerization process by evaluating the ability of factor XIIIa-crosslinked fibrinogen polymers to expose ‘fibrin-specific’ epitopes and enhance plasminogen activation. Crosslinked normal fibrinogen, fibrinogen with deficient [des Bβ1-42] or defective [Birmingham (AαR16H)] fibrin ‘D:E’ assembly sites (‘EA’), or with defective end-to-end self-association sites (‘D:D’) [Cedar Rapids (γR275C)], exposed both ‘fibrin-specific’ epitopes and enhanced tPA-dependent plasminogen activation, whereas non-crosslinked fibrinogens showed minimal or no such activities. Epitope expression in cross-linked fibrinogen was retained in the presence of the fibrin EA site peptide homolog, gly-pro-arg-pro (GPRP), which inhibits fibrin D:E association, except for the Aα148-160 epitope in des Bβ1-42 fibrinogen, which was not expressed. Fibrin prepared from crosslinked normal or abnormal fibrinogen, except for the des Bβ1-42 fibrin epitopes, which were reduced or absent, expressed ‘fibrin-specific’ epitopes even in the presence of GPRP, which otherwise impairs such expression in noncrosslinked fibrin. Epitope exposure in fibrin prepared from non-cross-linked fibrinogen was nearly normal in Cedar Rapids fibrin (heterozygous D:D defect), but reduced in Birmingham fibrin (heterozygous EA defect), nil in des Bβ1-42 fibrin (EA deficient), and absent in all cases in the presence of GPRP. In contrast, plasminogen activation stimula-tory activity that had been exposed in crosslinked normal fibrinogen or in crosslinked des Bβ1-42 or Cedar Rapids fibrin, was preserved to a large extent in the presence of GPRP, suggesting that once enhanced stimulatory activity and epitopes are exposed, they are not completely reversible. The findings indicate that end-to-end intermolecular associations (D:D) are not critical for ‘fibrin-specific’ epitope exposure, but that polymerization brought about in fibrinogen through factor XIIIa crosslinking, or in fibrin through ‘D:E’ interactions, is necessary for ‘fibrin-specific’ (more correctly, ‘polymerization-specific’) epitope exposure and enhancement of plasminogen activation.